(untitled) (Texas Journal of Medical Science, 2025)
Cardiac myxoma is the most common primary benign tumor of the heart. The disease can manifest itself as dizziness, spontaneous nocturnal shortness of breath and hemoptysis. The tumor can block the blood flow, leading to the death of the patient, so if symptoms appear, you should immediately consult a doctor. Myxoma can be located in any cavity of the heart, but most often affects the left or right atrium. The tumor grows on a leg, which is attached to a recess in the septum between the left and right parts of the heart. Often it has a smooth surface, but in a third of cases it is loose and villous